Well‐defined and robust rhodium catalysts for the hydroacylation of terminal and internal alkenes - Prades, A; Fernandez, M; Pike, S; Willis, M; Weller, A (Wiley, 2015)
A Rh‐catalyst system based on the asymmetric ligand tBu2PCH2P(o‐C6H4OMe)2 is reported that allows for the hydroacylation of challenging internal alkenes with β‐substituted aldehydes. Mechanistic studies point to the stabilizing role of both excess alkene and the OMe‐group.